A study on the borrowing patterns of the middle school students (Grades 4-7) of the Asterio J. Katigbak Educational Media Center (KEMC) of the Ateneo de Manila Grade School through analysis of book circulation - Albania, Pamela S. (2010)
The study was conducted in order to analyze the borrowing patterns of the middle school students (Grades 4-7) of the Asterio J. Katigbak Educational Media Center (KEMC) through analysis of book circulation. It was hypothesized that there is no significant relationship between book borrowing and the and the following: (1) student's grade level; (2) students' parent's profession or field, and; (3) age of materials. The study also determined the percentage of collection circulation by grade levels, the average circulation per volume, and the reading interests of middle school students.